Case Report: Lack of Response to Givosiran in a Case of ALAD Porphyria - Graff, Erica; Anderson, Karl E.; Levy, Cynthia (Frontiers in Genetics, 2022)
Introduction: 5-Aminolevulinic acid dehydratase (ALAD) porphyria (ADP) is an autosomal recessive disease characterized by a profound deficiency in ALAD, the second enzyme in the heme biosynthetic pathway, and acute neurovisceral attacks with abdominal pain and peripheral neuropathy. Hemin infusions are often effective in treating and preventing such attacks. Givosiran was recently approved for prevention of attacks of acute hepatic porphyrias (AHP), including ADP, but to our knowledge has not yet been applied in patients with this ultrarare disease. Case description: We update the clinical course and report new treatment outcomes of a 32-year-old man with ADP managed for many years with weekly prophylactic hemin infusions. He has developed evidence of iron overload and was more recently found to have compensated cirrhosis. The patient was started on givosiran (Givlaari™, Alnylam), a small interfering RNA (siRNA) therapeutic that is effective in preventing frequently recurring attacks of acute intermittent porphyria (AIP), the most common type of AHP. Discussion: No adverse effects of givosiran on the liver were observed in this patient with cirrhosis during 6 months of treatment with givosiran. The patient has continued to have recurrent attacks, with transient decreases in ALA levels only as related to treatment of his attacks with hemin. Our experience limited to one patient with ADP suggests that givosiran may not be effective in this type of acute porphyria. Since ADP may have an erythropoietic component, treatment with hydroxyurea, which was beneficial in one previous case, is planned.